Financial incentives for a healthy life style and disease prevention among older people: a systematic literature review. Issue 5 (August 2016) - Tambor, Marzena; Pavlova, Milena; Golinowska, Stanisława; Arsenijevic, Jelena; Groot, Wim
Abstract Background To motivate people to lead a healthier life and to engage in disease prevention, explicit financial incentives, such as monetary rewards for attaining health-related targets (e.g. smoking cessation, weight loss or increased physical activity) or disincentives for reverting to unhealthy habits, are applied. A review focused on financial incentives for health promotion among older people is lacking. Attention to this group is necessary because older people may respond differently to financial incentives, e.g. because of differences in opportunity costs and health perceptions. To outline how explicit financial incentives for healthy lifestyle and disease prevention work among older persons, this study reviews the recent evidence on this topic. Methods We applied the method of systematic literature review and we searched in PUBMED, ECONLIT and COCHRANE LIBRARY for studies focused on explicit financial incentives targeted at older adults to promote health and stimulate primary prevention as well as screening. The publications selected as relevant were analyzed based on directed (relational) content analysis. The results are presented in a narrative manner complemented with an appendix table that describes the study details. We assessed the design of the studies reported in the publications in a qualitative manner. We also checked the quality of our review using the PRISMA 2009 checklist. Results We identified 15 studies on the role of explicit financial incentives in changing health-related behavior of older people. They include both, quantitative studies on the effectiveness of financial rewards as well as qualitative studies on the acceptability of financial incentives. The quantitative studies are characterized by a great diversity of designs and provide mixed results on the effects of explicit financial incentives. The results of the qualitative studies indicate limited trust of older people in the use of explicit financial incentives for health promotion and prevention. Conclusions More research is needed on the effects of explicit financial incentives for prevention and promotion among older people before their broader use can be recommended. Overall, the design of the financial incentive system may be a crucial element in their acceptability.